Tolperisone in muscle tension - Kochanowski, Jan; Tomalka, Karol (Lekarz POZ, 2017)
Muscle tension is defined as the physiological state associated with the resistance encountered during passive movements in joints. Undoubtedly, a clinical problem is seen in patients with muscular tone disorders and among them patients with increased muscular tone in a type of spasticity. Among these are post-stroke patients, patients with multiple sclerosis, and patients after brain and spinal injuries. In order to reduce increased muscle tension, we use: pharmacological treatment, kinesis and physical therapy, and surgical treatment. Pharmacotherapy of increased spasticity of muscle tone includes the use of topical, intrathecal, and/or oral medications. The data concerning the efficacy and safety of treatment of increased muscle tone with tolperisone administered orally were presented.